A journey from Rio to Paris via Kyoto to facilitate technology transfer to the LDCs under the UNFCCC. Issue 1 (14th January 2021) - Azam, Monirul
Abstract : Purpose: The purpose of this study is to evaluate to what extent the Paris Agreement and the United Nations Framework Convention on Climate Change (UNFCCC) have supported (or could support) the least developed countries (LDCs) particularly for accessing the climate technologies and thereby to meet the objectives of the Paris Agreement. Design/methodology/approach: This study adopted legal dogmatism to evaluate the gradual development of technology transfer issues to support the LDCs under the international climate regime. Findings: This study suggested a few potential measures to facilitate meaningful technology transfer to LDCs – such as clarifying and linking the role of the technology and financial mechanism, a more robust role of capacity building, using the sustainable development mechanism with a technology transfer focus, improving the transparency and reporting mechanism to particularly indicate support regarding technology transfer requested and received by the LDCs linking it with the nationally determined contributions, and adapting a pragmatic approach to intellectual property. Originality/value: This study is an original contribution as it identified concern over technology transfer under the UNFCCC since 1992 with a focus on the LDCs and indicated required actions that need to be taken to support the LDCs in the context of climate-related technology transfer and beyond.